Peran Lembagakeuangan Publik Islam dalam Pemberdayaan Ekonomi Masyarakat - Rahmani Timorita Yulianti (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The article discusses about the role of public Moslem finance institution viewed in the context of economic public endeavor. This problem emerges in public because the public Moslem finance institution in Indonesia does not take in part proportionally yet to mate public prosperity in Indonesia whereas the research of the language and literature Center in UIN by Syarif Hidayat¬ullah and Ford Foundation results that the potention of funds (Zakat, Infak, Shodaqoh) and donation of Moslems in Indonesia (amount Rp 19.3 billions) managed by the public Moslem finance institution can be used for people prosperity. Besides, it is supported with the big number of Moslems in Indonesia. Therefore, there are two important things to be focused on this article. First, why can't the fund in public Moslem finance institution, like ZIS and donation, in Indonesia be more efficient in a maximum way to realize the prosperity? Then, how to develop the public finance institution in Indonesia?Keywords: infak,sedekah, Indonesia, zakat